Public Relations Campaign Management for Supporting Responsible and Sustainable Tourism - Melati Andria Widanarko; Gayatri Atmadi (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2023)
Local community in Thousand Islands should know how to manage public relations campaign properly for supporting responsible and sustainable tourism. This research aims to know how Jejak Seribu can involve youth  community in Tidung Island in  managing  public relations campaign for  education exploration :  Jelajah Edukasi : Entrepreneur Millenials 2019. This study uses qualitative-descriptive research approach with case study. The method of data collection in this study is in-depth interviews with the head of Jejak Seribu, the head of entrepreneurship division of Jejak Seribu, and members of Jejak Seribu. The results of this study show that Jejak Seribu has  implemented the stages of campaign management in conducting the Entrepreneur Millennials campaign, and the application of the concept of responsible tourism, sustainable tourism and public relations campaign proves more effective in achieving campaign objectives.This  research only focused on the very specific program of "Jelajah Edukasi Jejak Seribu: Entrepreneur Millenials 2019" conducted in Tidung Island. This study has a small sample size that may not  represent the  population. This study is expected to provide  useful insights for any community in the management of public relations campaign.